On the international dissemination of technology news shocks - Jo\~ao C. Claudio; Gregor von Schweinitz (Halle Institute for Economic Research (IWH), 2020)
This paper investigates the propagation of technology news shocks within and across industrialised economies. We construct quarterly utilisation-adjusted total factor productivity (TFP) for thirteen OECD countries. Based on country-specific structural vector autoregressions (VARs), we document that (i) the identified technology news shocks induce a quite homogeneous response pattern of key macroeconomic variables in each country; and (ii) the identified technology news shock processes display a significant degree of correlation across several countries. Contrary to conventional wisdom, we find that the US are only one of many different sources of technological innovations diffusing across advanced economies. Technology news propagate through the endogenous reaction of monetary policy and via trade-related variables. That is, our results imply that financial markets and trade are key channels for the dissemination of technology.
urn:nbn:de:gbv:3:2-128944
Keywords: E24; E32; F41; 330; technology news shocks; technology spillover; structural VAR; international trade